An exploratory study of the adoption of mobile telecommunications service in order to improve mobile health service development - Grego-Nagel, Anne C. (Kansas State University, 2016)
This dissertation is the result of exploring the phenomenon of the adoption of a service innovation, in particular mobile telecommunications service, with the goal of informing the design of mobile health services. A grounded research study led to the finding that older adults may not abandon a legacy service, such as landline telecommunications service, when they adopted mobile telecommunications service. To further understand the results of the first study, a multidisciplinary literature review was undertaken and resulted in a typology of the factors of individual-level innovation adoption that can be applied by human factors professionals in the field. The three categories of factors included macro environmental, innovation-specific, and human factors. A research analysis of a study done by a county health department provided insights into what older adults contributed to the service production process in healthcare services including which common proxies do not accurately reflect the situations of older adults. A three-state process model of individual-level innovation adoption, which incorporated the role of a legacy system, was developed using the adoption patterns of mobile telecommunications services. In this model, individuals move from a state of using a legacy system to adopting a innovative system while still using the legacy system. After a period of time, the individual moves from the state of dual use to fully abandoning the legacy system and using only the innovative system. A compartmental mathematical model is developed to allow the model to be simulated and future service demand needs can be better predicted. Two decision-making processes were identified to be employed by individuals in the abandonment of a landline telecommunications services. Finally, recommendations for the design of mobile health services are provided.
Keywords: Industrial engineering; Human factors; Innovation